0587 Sleep Problems are Associated with Treatment for Anemia in the US Population. (25th May 2022) - Shah, Sayani; Mason, Brooke; Wills, Chloe; Tubbs, Andrew; Killgore, William; Grandner, Michael
Abstract: Introduction: Anemia is characterized as low circulating hemoglobin and is often treated with an increase in iron consumption. Previous studies have linked anemia with Restless Legs Syndrome. Regarding other sleep disorders, Insomnia has been found to be associated with anemia in children, but the relationship has been understudied in adults. Methods: A multinomial logistic regression was conducted on the data collected from 2017 to March 2020 for the National Health and Nutrition Examination Survey, to explore a relationship between those with self-assessed sleep problems and whether the participant was treated for anemia. Sleep problems were assessed using a item asking participants how often they have been bothered by difficulties "falling asleep, staying asleep, or sleeping too much, " categorized as "Never, " "Several Days, " "More Than Half the Days" and "Nearly Every Day" in the past 2 weeks. Anemia treatment was characterized as "yes" or "no" based on self-report, with any form of treatment in the past 3 months was considered as "yes." Reported results were unweighted; weighted results forthcoming. Results: Unadjusted results indicate that those being treated for anemia show an increased likelihood of sleep difficulties several days (OR:1.36, [1.07, 1.73] p=0.011), more than half the days (OR: 1.59, [1.13, 2.25] p=0.008), and nearly every day (OR: 1.85, [1.37, 2.50] p<0.001), compared to those who report that they never have sleep difficulties. When adjusted for sex, age, race/ethnicity, education, and marital status, those being treated for anemia show significant increased odds of sleep problems several days (OR: 1.29, [1.01, 1.65] p=0.041), more than half the days (OR: 1.50, [1.06, 2.14] p=0.024), and nearly every day (OR: 1.55, [1.13, 2.13] p=0.006), compared to never. Those being treated for anemia also had a higher likelihood of having short sleep (≤ 6 hours) during the week (OR: 1.56, [1.13, 2.15], p=0.007) as well as long sleep( ≥ 9 hours) (OR: 1.75, [1.30, 2.36], p<0.001) compared to those that slept a healthy amount, 6.5-8.5 hours a night. Conclusion: There was a significant relationship between those treated for anemia the presence of sleep difficulties, as well as short and long sleep. Future studies should assess the associations between anemia and specific sleep characteristics, as sleep problems may be a cause, a consequence, or a marker of anemia. Also, the degree to which these sleep difficulties represent overlap with Restless Legs symptoms should be explored at the population level. Support (If Any):